The compliance of hand hygiene among Professional nurses influenced by knowledge of precaution standards, attitude, and motivation - Arthur, Andre; Rina Mutiara; Andry (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: Hospital infections are one of the most important issues in patient safety aspects in hospitals. The standard precautions are designed to reduce the risk of infection with infectious diseases to be applied routinely in the care of the entire patient in the hospital. Objective: The aim of this study is to examine the association between standards of knowledge, attitudes, and motivation of nurses on compliance with hand hygiene. Method: A cross-sectional study was apllied in this study. We involved 45 professiona nurses who has working at inpatients room at Sentra Medika Hospital, Karawang, Indonesia. Result: There is a significant influence of knowledge of precaution standards, attitude and motivation of nurses work on the observance of performing hand hygiene simultaneously (p-value<0.05). Conclusion: The standard knowledge of precaution, attitude, and nurses’ motivation is crucial point to prevent the infection. The massive contribution of the influence of standard knowledge of precaution, attitude, and motivation of nurses to the observance of hand hygiene was 93.7%. Implication: For clinical practice need to regular training for all nurses to enhance knowledge, the need for management support in organizing and motivating nursing to follow basic infection prevention and control nurses (IPCN). Further study also needs to explore deeply the effect of those factors in qualitatively and develop some program to ensure hand hygiene implementation regularly implemented through hospital unit